Patient-specific online dose verification based on transmission detector measurements - Thölking, Johannes; Fleckenstein, Jens; Sekar, Yuvaraj; Lohr, Frank; Wenz, Frederik; Wertz, Hansjörg (Radiotherapy and oncology, 2016)
Background and purpose - Since IMRT-techniques lead to an increasingly complicated environment, a patient specific IMRT-plan verification is recommended. Furthermore, verifications during patient irradiation and 3D dose reconstruction have the potential to improve treatment delivery, accuracy and safety. This study provides a detailed investigation of the new transmission detector (DTD) Dolphin (IBA Dosimetry, Germany) for online dosimetry. - Materials and methods - The clinical performance of the DTD was tested by dosimetric plan verification in 2D and 3D for 18 IMRT-sequences. In 2D, DTD measurements were compared to a pre-treatment verification method and a treatment planning system by gamma index and dose difference evaluations. In 3D, dose-volume-histogram (DVH) indices and gamma analysis were evaluated. Furthermore, the error detection ability was tested with leaf position uncertainties and deviations in the linear accelerator (LINAC) output. - Results - The DTD measurements were in excellent agreement to reference measurements in both 2D (γ3%,3mm=(99.7±0.6)% <1, ΔD±5%=(99.5±0.5)%) and 3D. Only a small dose underestimation (<2%) within the target volume was observed when analyzing DVH-indices. Positional errors of the leaf banks larger than 1mm and errors in LINAC output larger than 2% were identified with the DTD. - Conclusions - The DTD measures the delivered dose with sufficient accuracy and is therefore suitable for clinical routine.